Analysis of Global Startup Market - Minasyan, Anna; Martirosyan, Mariam («Տնտեսագետ» հրատ․)
Alongside with the technological progress, the world economy presents new requirements and issues, which become solvable under the conditions of creation and implementation of innovative ideas. Within the framework of this research, a historical reference has been made to the history of the creation of startups and the formation of the startup ecosystem, as well as the characteristics of startups, stages of development, sources of financing, reasons for failure and the most successful projects are considered, thereby identifying the sectors of the economy that are most promising for the development of startups. By conducting a detailed study on the global market of startups, the trends of their development, the progress registered in the startup ecosystem in recent years, according to economic sectors, countries and individual cities, have been highlighted. Within the framework of the analysis of the global market of startups, a comprehensive reference is made to the Armenian startup ecosystem, the trends of its development and the main sources of financing, as well as the Armenian startup projects, that gained world recognition, have been studied. The results of the research show that along with the progress of time, the development of the startup market is becoming more and more demanded and its impact on global economic development is increasing.
Keywords: International economics